Metal vacancy MXene-polyaniline composite material as well as preparation method and application thereof

Polyaniline is loaded on the MXene sheet layer through in-situ polymerization, forming a metal vacant MXene-polyaniline composite material, which solves the problem of the unutilized energy storage potential of MXene materials and poor structural stability, and achieves the improvement of energy storage performance and structural stability.

CN120072896APending Publication Date: 2025-05-30JIANGXI SCI & TECH NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510234423.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

The energy storage potential of the transition metal layer is underutilized due to surface end groups coverage. At the same time, the strong interaction between nanoscale sheets leads to the re-stack of two-dimensional structures, which reduces the structural utilization and stability and limits the performance of energy storage performance.

Method used

Multi-layer MXene Mo4/3CTx was obtained by etching Mo4/3Sc2/3AlC by hydrofluoric acid, and adding an intercalating agent to obtain a small layer of MXene Mo4/3CTx. It was then mixed with aniline, hydrochloric acid and ammonium persulfate for in-situ polymerization to form polyaniline and loaded on the MXene sheet layer to form a metal vacant MXene-polyaniline composite.

Benefits of technology

This method effectively prevents re-stack between MXene sheets, maintains the layered structure, improves energy storage performance and structural stability, and enhances the conductivity and ion conductivity of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072896A_ABST
    Figure CN120072896A_ABST
Patent Text Reader

Abstract

The invention relates to the field of aqueous batteries, in particular to a metal vacancy MXene-polyaniline composite material as well as a preparation method and application thereof. The Mo4 / 3Sc2 / 3AlC is subjected to etching treatment, and multiple layers of MXene Mo4 / 3CTx are obtained; the multi-layer MXene Mo4 / 3CTx is subjected to intercalation treatment, and a few-layer MXene Mo4 / 3CTx is obtained; aniline, hydrochloric acid, ammonium persulfate and the few-layer MXene Mo4 / 3CTx are mixed and then subjected to an in-situ polymerization reaction, and the metal vacancy MXene-polyaniline composite material is obtained. According to the metal vacancy MXene-polyaniline composite material, the problem that the energy storage potential of a transition metal layer is limited due to surface end group covering of MXene is solved, re-stacking of MXene sheet layers is prevented, and the energy storage performance and the structural stability of the metal vacancy MXene-polyaniline composite material are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aqueous batteries, and in particular to a metal vacancy MXene-polyaniline composite material and a preparation method and application thereof. Background Art

[0002] In recent years, new aqueous rechargeable batteries (ARBs) have gained wide attention and favor due to their low cost, inherent safety, environmental friendliness and excellent electrochemical performance. In this field, aqueous ammonium ion batteries (AIBs) have become an increasing research hotspot due to the cost-effectiveness, low molar mass and fast diffusion kinetics of ammonium ions. However, AIBs are still in the early stages of development, and the research and development of high-performance cathode materials has become a key factor restricting their further development.

[0003] Among them, MXenes, a new type of two-dimensional (2D) transition metal carbonitrides, have attracted much attention since their discovery in 2011 due to their unique physical and chemical properties, such as excellent mechanical strength, high metallic conductivity, rich surface functional groups, and good hydrophilicity. In recent years, MXenes have shown broad application prospects in the field of electrode materials for aqueous ion batteries. However, the MXene surface is covered by end groups, resulting in the energy storage potential of the MXene transition metal layer not being fully utilized; at the same time, there are strong interactions between the nanoscale sheets of MXene, and the two-dimensional sheet structure is easy to restack to form a multilayer or even three-dimensional bulk structure. This stacking phenomenon not only reduces the utilization rate of the MXenes layered structure, but also reduces its active sites and affects its structural stability, thereby restricting the full utilization of the MXenes energy storage performance. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a metal vacancy MXene-polyaniline composite material and a preparation method and application thereof. 4 / 3 Sc 2 / 3 AlC, to obtain multilayer MXene Mo 4 / 3 CT x ; Then, multilayer MXene Mo 4 / 3 CT x Add intercalation agent to obtain few-layer MXene Mo 4 / 3 CT x , aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT xAfter mixing, an in-situ polymerization reaction is carried out to obtain a metal vacancy MXene-polyaniline composite material. The metal vacancy MXene-polyaniline composite material prepared by the preparation method of the present invention not only overcomes the problem that the energy storage potential of the transition metal layer of MXene is not fully utilized due to the coverage of surface end groups, but also uniformly coats polyaniline on the nanoscale sheets of MXene through an in-situ polymerization reaction, effectively preventing the re-stacking between the sheets, maintaining the layered structure of MXenes, and realizing the simultaneous improvement of the energy storage performance and structural stability of the metal vacancy MXene-polyaniline composite material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first object of the present invention is to provide a preparation method of a metal vacancy MXene-polyaniline composite material, comprising the following steps:

[0007] S1. Mix hydrofluoric acid, Mo 4 / 3 Sc 2 / 3 AlC and carry out an etching treatment. During the etching treatment, hydrofluoric acid is used as an etchant to etch away the Al layer and Sc layer of Mo 4 / 3 Sc 2 / 3 AlC to obtain multilayer MXene Mo 4 / 3 CT x .

[0008] S2. Add an intercalating agent to the multilayer MXene Mo 4 / 3 CT x . The intercalating agent molecules enter the interlayer space of MXene, and the interaction force between the intercalating agent molecules and the MXene layers overcomes the van der Waals force between the layers, so that the MXene layers are peeled off and dispersed to obtain few-layer MXeneMo 4 / 3 CT x ; when directly carrying out in-situ polymerization on multilayer MXene, not only the energy storage performance of the large specific surface area of MXene cannot be fully exerted, but also the loading of polyaniline will be affected due to the surface accumulation of MXene, resulting in the influence on the performance of the overall metal vacancy MXene-polyaniline composite material.

[0009] S3. Mix aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x and carry out an in-situ polymerization reaction. During the in-situ polymerization reaction, hydrochloric acid and ammonium persulfate jointly act as initiators. Hydrochloric acid provides an acidic environment, and ammonium persulfate decomposes to generate free radicals under acidic conditions, promoting the conversion of aniline into polyaniline through a free radical chain reaction and loading it on few-layer MXeneMo 4 / 3 CT xOn the nanolayered structure, a metal vacancy MXene-polyaniline composite material is obtained; wherein, the mass ratio of aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x is 1:3:0.5:5-10; taking the content of MXene Mo 4 / 3 CT x as the standard, too much or too little dosage will cause the morphology change of polyaniline on the surface of MXene Mo 4 / 3 CT x ; when the dosage is too little, the distribution is uneven; when the dosage is too much, it will lead to accumulation and make the dispersion worse.

[0010] Preferably, the mass ratio of aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x is 1:3:0.5:8.

[0011] Preferably, the conditions for the in-situ polymerization reaction are: stirring at -5°C to 0°C for 12h to 15h.

[0012] Preferably, the mass ratio of hydrofluoric acid to Mo 4 / 3 Sc 2 / 3 AlC is 4.8-10.2:1-2; at this mass ratio, the etched multi-layer MXene Mo 4 / 3 CT x has a high yield and less loss.

[0013] Preferably, the operation of the etching treatment is: mixing hydrofluoric acid and Mo 4 / 3 Sc 2 / 3 AlC, and stirring at 30°C to 35°C for 24h to 36h; wherein, the mass ratio of hydrofluoric acid to Mo 4 / 3 Sc 2 / 3 AlC is 4.8-10.2:1-2.

[0014] Preferably, the intercalation treatment method is: adding an intercalating agent to multi-layer MXene Mo 4 / 3 CTx, mixing evenly and then obtaining it through centrifugation and washing; wherein, the dosage ratio of the intercalating agent to multi-layer MXene Mo 4 / 3 CT x is 5mL-7mL:1g-2g.

[0015] Preferably, the intercalating agent is selected from cationic surfactants or organic bases.

[0016] Preferably, the cationic surfactant is selected from alkylamine salts or quaternary ammonium salts.

[0017] Preferably, the organic base is selected from tetrabutylammonium hydroxide, isopropylamine or n-butylamine.

[0018] Preferably, the mass fraction of hydrofluoric acid is 48% to 51%; among them, when the mass fraction of hydrofluoric acid is lower than 48%, the etching process is incomplete; when the mass fraction of hydrofluoric acid is higher than 51%, the etching process is violent, resulting in over-etching, which leads to a decrease in the yield of multi-layer MXene Mo 4 / 3 CT x .

[0019] Preferably, the conditions for the mixing treatment are: stirring at a stirring rate of 400 rpm to 600 rpm for 10 min to 15 min.

[0020] The second object of the present invention is to provide a metal vacancy MXene-polyaniline composite material prepared by the above preparation method.

[0021] Preferably, in the metal vacancy MXene-polyaniline composite material, the metal vacancy MXene and polyaniline are in-situ composite, the polyaniline is in a sheet-like shape, and the sheet-like polyaniline is vertically dispersed on the surface of the MXene sheet.

[0022] The third object of the present invention is to provide the application of the above metal vacancy MXene-polyaniline composite material in the preparation of a positive electrode material for an aqueous ammonium ion battery.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] 1. The present invention provides a preparation method of a metal vacancy MXene-polyaniline composite material, etching Mo 4 / 3 Sc 2 / 3 AlC to obtain multi-layer MXene Mo 4 / 3 CT x ; intercalating the multi-layer MXene Mo 4 / 3 CT x to obtain few-layer MXene Mo 4 / 3 CT x ; mixing aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x , and then carrying out an in-situ polymerization reaction to generate polyaniline, and the polyaniline is loaded on the nano-layered structure of few-layer MXene Mo 4 / 3 CT x to obtain a metal vacancy MXene-polyaniline composite material; among them, aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT xThe mass ratio is 1:3:0.5:5 - 10. The metal vacancy MXene-polyaniline composite material prepared by the preparation method of the present invention not only overcomes the problem that the energy storage potential of the transition metal layer of MXene is not fully utilized due to the coverage of surface end groups, but also uniformly coats polyaniline on the nanoscale sheets of MXene through in-situ polymerization reaction, effectively preventing the re-stacking between the sheets, maintaining the layered structure of MXenes, and realizing the simultaneous improvement of the energy storage performance and structural stability of the metal vacancy MXene-polyaniline composite material.

[0025] 2. The metal vacancy MXene-polyaniline composite material prepared by the present invention has high conductivity. In the composite material, polyaniline is vertically dispersed in the form of sheets on the surface of the MXene Mo 4 / 3 CT x sheets, endowing the metal vacancy MXene-polyaniline composite material with good ion conduction and battery transport performance; at the same time, polyaniline plays an effective pillar support role in the MXene Mo 4 / 3 CT x sheet structure, thus significantly enhancing the structural stability of the metal vacancy MXene-polyaniline composite material. In addition, as a high-performance conductive polymer, polyaniline further enhances the conductivity of the metal vacancy MXene-polyaniline composite material, promotes the transport of charges in the metal vacancy MXene-polyaniline composite material, and thus significantly improves the energy storage performance of the metal vacancy MXene-polyaniline composite material in aqueous ion batteries.

[0026] 3. In the structure of the metal vacancy MXene-polyaniline composite material of the present invention, the metal vacancies are mainly located in the transition metal layer of MXene. The existence of these metal vacancies enables some of the transition metal atoms originally covered by surface end groups to be partially exposed. This exposure not only activates the electrochemically active sites on the transition metal layer of the MXene material, but also significantly improves the comprehensive electrochemical performance of the MXene material, including the transport performance of electrons and ions and the stability of the material. In addition, the metal vacancy MXene-polyaniline composite material prepared by the present invention shows great application potential in the field of aqueous batteries due to its intrinsic hydrophilicity. Description of the Drawings

[0027] Figure 1 XRD patterns of the metal vacancy MXene-polyaniline composite material prepared in Example 1, MXene Mo 4 / 3 CT x and PANI prepared in Comparative Example 1.

[0028] Figure 2 XRD patterns of the metal vacancy MXene-polyaniline composite material prepared in Example 1, MXene Mo 4 / 3CT x and the FTIR diagram of PANI prepared in Comparative Example 1.

[0029] Figure 3 SEM diagram of the metal vacancy MXene-polyaniline composite material prepared in Example 1.

[0030] Figure 4 SEM diagram and elemental EDS distribution diagram of the metal vacancy MXene-polyaniline composite material prepared in Example 1, where (a) is the SEM diagram, (b) is the Mo element, (c) is the C element, (d) is the O element, (e) is the F element, and (f) is the N element.

[0031] Figure 5 XPS diagram of Mo in the metal vacancy MXene-polyaniline composite material prepared in Example 1.

[0032] Figure 6 NH in the metal vacancy MXene-polyaniline composite material prepared in Example 1 under different voltages 4 + ex-situ XRD diagram, where (a) is the matching GCD curve diagram at 0.1 A / g, and (b) is the ex-situ XRD diagram.

[0033] Figure 7 For the metal vacancy MXene-polyaniline composite material and MXene Mo prepared in Example 1 4 / 3 CT x and the test diagrams of the aqueous ammonium ion battery performance of PANI prepared in Comparative Example 1, where (a) is the CV curve comparison diagram, (b) is the EIS curve comparison diagram, (c) is the charge-discharge curve diagram, and (d) is the charge-discharge cycle stability diagram. Detailed implementation manners

[0034] Next, the technical solutions of the present invention will be clearly and completely described in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.

[0035] In the prior art, as a class of two-dimensional transition metal carbonitrides with excellent properties, MXenes have shown great potential in the field of electrode materials for aqueous ion batteries. However, the surface end-group coverage of MXene limits the energy storage capacity of its transition metal layer. At the same time, the strong interaction between MXene nanosheets leads to the easy re-stacking of the two-dimensional structure, reducing the structural utilization rate, reducing the active sites and affecting the structural stability, thus restricting the full play of the energy storage performance of MXenes.

[0036] In view of the above technical deficiencies, the present invention provides a method for preparing a metal vacancy MXene-polyaniline composite material, comprising the following steps: etching Mo 4 / 3 Sc 2 / 3 AlC to obtain multi-layer MXene Mo 4 / 3 CT x ; intercalating the multi-layer MXene Mo 4 / 3 CT x to obtain few-layer MXene Mo 4 / 3 CT x ; mixing aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x and carrying out an in-situ polymerization reaction to generate polyaniline, with the polyaniline being loaded on the nano-layered structure of few-layer MXene Mo 4 / 3 CT x to obtain a metal vacancy MXene-polyaniline composite material; wherein, the mass ratio of aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x is 1:3:0.5:5-10.

[0037] The metal vacancy MXene-polyaniline composite material prepared by the preparation method of the present invention not only overcomes the problem that the energy storage potential of the transition metal layer of MXene is not fully utilized due to the coverage of surface end groups, but also uniformly coats polyaniline on the nano-scale lamellae of MXene through an in-situ polymerization reaction, effectively preventing the re-stacking between the lamellae, maintaining the layered structure of MXenes, and realizing the simultaneous improvement of the energy storage performance and structural stability of the metal vacancy MXene-polyaniline composite material.

[0038] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0039] Example 1

[0040] A method for preparing a metal vacancy MXene-polyaniline composite material, comprising the following steps:

[0041] S1. At 30 °C, 2 g of MAX phase Mo 4 / 3 Sc 2 / 3The AlC powder was slowly added to 20 mL of a 48% hydrofluoric acid solution under continuous stirring, and the stirring rate was controlled at 100 rpm / min. After all the addition, stirring was continued for 24 h to carry out the etching process of the MAX phase. After the etching was completed, centrifugation was carried out at 6000 rpm / min for 4 min. After centrifugation, the resulting black-brown precipitate was washed with deionized water until it was nearly neutral to obtain multi-layer MXene Mo 4 / 3 CT x .

[0042] S2. 7 mL of tetrabutylammonium hydroxide intercalating agent was added to 2 g of the multi-layer MXene Mo 4 / 3 CT x to ensure complete immersion, and it was shaken well for 10 min. Then, centrifugation was carried out at 6000 rpm / min for 4 min. After centrifugation was completed, 30 mL of deionized water was added and shaken for another 10 min, and then centrifugation was carried out at 2500 rpm / min for 30 min. The upper suspension was taken to obtain few-layer MXene Mo 4 / 3 CT x , denoted as Mo 4 / 3 C.

[0043] S3. After ultrasonically dispersing 20 mg of aniline in deionized water for 10 min, 100 g of the few-layer MXene Mo 4 / 3 CT x was added to the dispersion. After stirring evenly, it was placed in a refrigerator and refrigerated at 5 °C for 15 min. Then, it was quickly added to 10 mL of a 1 mol / L HCl solution containing 735.128 mg of ammonium persulfate, and stirring was continued for 5 min. Then, the reaction system was placed in an ice bath at -5 °C for a polymerization reaction for 13 h. After the reaction was completed, centrifugation was carried out at 6500 rpm / min for 4 min. After centrifugation, the black precipitate was washed successively with deionized water and absolute ethanol until the filtrate was neutral. Then, vacuum drying was carried out at 60 °C for 12 h to obtain a metal vacancy MXene-polyaniline composite material, denoted as M:P = 5:1.

[0044] Example 2

[0045] A preparation method of a metal vacancy MXene-polyaniline composite material, comprising the following steps:

[0046] S1. At 35 °C, 1 g of the MAX phase Mo 4 / 3 Sc 2 / 3The AlC powder was slowly added to 10 mL of a hydrofluoric acid solution with a mass fraction of 51% under continuous stirring, and the stirring rate was controlled at 200 rpm / min; after all the addition, stirring was continued for 36 h to carry out the etching process of the MAX phase; after the etching was completed, centrifugation was carried out at 6000 rpm / min for 4 min; after centrifugation, the resulting black-brown precipitate was washed with deionized water until it was nearly neutral to obtain multi-layer MXene Mo 4 / 3 CT x 。

[0047] S2. To 1 g of the multi-layer MXene Mo 4 / 3 CT x 5 mL of tetrabutylammonium hydroxide intercalating agent was added to ensure complete immersion, and it was shaken well for 10 min, then centrifuged at 6000 rpm / min for 4 min; after centrifugation, 30 mL of deionized water was added and shaken for another 10 min, then centrifuged at 2500 rpm / min for 30 min, and the upper suspension was taken to obtain few-layer MXene Mo 4 / 3 CT x ,denoted as Mo 4 / 3 C。

[0048] S3. After ultrasonically dispersing 20 mg of aniline in deionized water for 10 min, 100 g of the few-layer MXene Mo 4 / 3 CT x was added to the dispersion. After stirring evenly, it was placed in a refrigerator and refrigerated at 0 °C for 15 min; then, 10 mL of a 1 mol / L HCl solution containing 735.128 mg of ammonium persulfate was quickly added, and after continuing to stir for 5 min, the reaction system was placed in an ice bath at 0 °C for a polymerization reaction for 15 h; after the reaction was completed, centrifugation was carried out at 6500 rpm / min for 4 min; after centrifugation, the black precipitate was washed successively with deionized water and absolute ethanol until the filtrate was neutral; then, vacuum drying was carried out at 60 °C for 12 h to obtain a metal vacancy MXene-polyaniline composite material.

[0049] Example 3

[0050] A preparation method of a metal vacancy MXene-polyaniline composite material, comprising the following steps:

[0051] S1. At 30 °C, 2 g of the MAX phase Mo 4 / 3 Sc 2 / 3AlC powder was slowly added to 20 mL of hydrofluoric acid solution with a mass fraction of 48% under continuous stirring, and the stirring rate was controlled at 100 rpm / min; after all was added, stirring continued for 24 h to carry out the etching process of the MAX phase; after the etching was completed, centrifugation was carried out at 6000 rpm / min for 4 min; after centrifugation, the resulting black-brown precipitate was washed with deionized water until nearly neutral to obtain multilayer MXene Mo 4 / 3 CT x 。

[0052] S2. Add 7 mL of tetrabutylammonium hydroxide intercalating agent to 2 g of multilayer MXene Mo 4 / 3 CT x to ensure complete immersion, and shake well for 10 min, then centrifuge at 6000 rpm / min for 4 min; after centrifugation is completed, add 30 mL of deionized water and continue to shake for 10 min, then centrifuge at 2500 rpm / min for 30 min, and take the upper suspension to obtain few-layer MXene Mo 4 / 3 CT x ,denoted as Mo 4 / 3 C。

[0053] S3. After ultrasonic dispersing 20 mg of aniline in deionized water for 10 min, add 200 g of few-layer MXene Mo 4 / 3 CT x to the dispersion, stir evenly and then place it in the refrigerator at 5 °C for 15 min; then, quickly add it to 10 mL of 1 mol / L HCl solution containing 735.128 mg of ammonium persulfate, continue to stir for 5 min, and then place the reaction system in an ice bath at -5 °C for polymerization reaction for 13 h; after the reaction is completed, centrifuge at 6500 rpm / min for 4 min; after centrifugation, wash the black precipitate with deionized water and anhydrous ethanol in turn until the filtrate is neutral; then carry out vacuum drying at 60 °C for 12 h to obtain the metal vacancy MXene-polyaniline composite material.

[0054] Example 4

[0055] A preparation method of a metal vacancy MXene-polyaniline composite material, comprising the following steps:

[0056] S1. At 30 °C, add 2 g of MAX phase Mo 4 / 3 Sc 2 / 3AlC powder was slowly added to 20 mL of hydrofluoric acid solution with a mass fraction of 48% under continuous stirring, and the stirring rate was controlled at 100 rpm / min; after all was added, stirring was continued for 24 h to carry out the etching process of the MAX phase; after etching, centrifugation was carried out at 6000 rpm / min for 4 min; after centrifugation, the resulting black-brown precipitate was washed with deionized water until nearly neutral to obtain multi-layer MXene Mo 4 / 3 CT x .

[0057] S2. 7 mL of tetrabutylammonium hydroxide intercalating agent was added to 2 g of multi-layer MXene Mo 4 / 3 CT x to ensure complete immersion, and it was shaken vigorously for 10 min, then centrifuged at 6000 rpm / min for 4 min; after centrifugation, 30 mL of deionized water was added and shaken for another 10 min, then centrifuged at 2500 rpm / min for 30 min, and the upper suspension was taken to obtain few-layer MXene Mo 4 / 3 CT x , denoted as Mo 4 / 3 C.

[0058] S3. After ultrasonically dispersing 20 mg of aniline in deionized water for 10 min, 160 g of few-layer MXene Mo 4 / 3 CT x was added to the dispersion, and after stirring evenly, it was placed in a refrigerator and refrigerated at 5 °C for 15 min; then, 10 mL of 1 mol / L HCl solution containing 735.128 mg of ammonium persulfate was quickly added, and after continuing to stir for 5 min, the reaction system was placed in an ice bath at -5 °C for a polymerization reaction for 13 h; after the reaction, centrifugation was carried out at 6500 rpm / min for 4 min; after centrifugation, the black precipitate was washed successively with deionized water and absolute ethanol until the filtrate was neutral; then, vacuum drying was carried out at 60 °C for 12 h to obtain a metal vacancy MXene-polyaniline composite material.

[0059] Comparative Example 1

[0060] A method for preparing polyaniline, comprising the following steps:

[0061] 1 g of aniline monomer was ultrasonically dispersed (for 10 min) in 50 mL of 3 mol / L HCl (prepared by diluting 12.5 mL of 12 mol / L HCl to 50 mL). Under stirring, 30 mL of 1 mol / L HCl solution containing 7.3 g of ammonium persulfate was rapidly added. After stirring thoroughly for 5 min, the reaction system was placed in an ice bath at -5 °C for a polymerization reaction for 13 h. After the reaction, centrifugation was carried out at 6500 rpm / min for 4 min. After centrifugation, the black precipitate was washed successively with deionized water and absolute ethanol until the filtrate was neutral. Then, vacuum drying was carried out at 60 °C for 12 h to obtain polyaniline, denoted as PANI.

[0062] Take 1 mL of MXene Mo prepared in Example 1 4 / 3 CT x Vacuum filtration was carried out on the filter membrane, and the weight of the film obtained after vacuum drying was measured to determine the concentration of MXene Mo 4 / 3 CT x .

[0063] Combined with Figure 1 and Figure 2 it was concluded that polyaniline was successfully loaded on the surface of MXene Mo 4 / 3 CT x , and it was observed that Figure 1 it was concluded that, relative to Mo 4 / 3 CT x , the diffraction peak of the (002) crystal plane of the metal vacancy MXene-polyaniline composite shifted significantly towards a lower angle. This phenomenon indicates that the interlayer spacing of the metal vacancy MXene-polyaniline composite has expanded, thereby increasing the interlayer spacing of MXene Mo 4 / 3 CT x at small angles.

[0064] It was observed that Figure 3 MXene Mo 4 / 3 CT x had a layered structure and was stacked in few layers; polyaniline was vertically dispersed in the form of nano-sheets on the surface of MXene Mo 4 / 3 CT x .

[0065] It was observed that Figure 4 the uniform distribution of Mo element, C element, O element and N element further proved that polyaniline was loaded on MXene Mo 4 / 3 CT x .

[0066] Preparation of the test electrode: Cut a titanium foil metal film with a size of 15 cm × 7 cm × 0.001 cm, wipe off the surface impurities with ethanol, and dry it naturally to obtain a clean titanium foil substrate material; Mix the metal vacancy MXene-polyaniline composite material (70%) prepared in Example 1, carbon black (20%), and the binder polyvinylidene fluoride (10%) in N-methylpyrrolidone, stir well to obtain a paste, then coat it on the dried titanium foil, vacuum dry it at 100 °C for 12 h, and then punch it into a disc with a diameter of 6 mm. The content of the metal vacancy MXene-polyaniline composite material on the titanium foil metal film is about 0.20 mg, and a metal vacancy MXene-polyaniline composite material electrode is obtained; Among them, the mass-volume ratio of the metal vacancy MXene-polyaniline composite material to N-methylpyrrolidone is 100 mg: 350 μL.

[0067] Respectively use the MXene Mo prepared in Example 1 4 / 3 CT x 、the PANI prepared in Comparative Example 1, and the metal vacancy MXene-polyaniline composite material electrode as the working electrode, use the Ag / AgCl electrode as the reference electrode, and use the glassy carbon electrode as the counter electrode. Place one end of the working electrode, reference electrode, and counter electrode in a mixed electrolyte of 1 mol / L ammonium sulfate and 0.1 mol / L sulfuric acid, and the other end is electrically connected to the French Bio-Logic electrochemical workstation SP-300 together to study its ammonium storage performance.

[0068] Use the XPS analysis method to study the behavior of ammonium ions during the discharge and charge processes, and observe Figure 5 It is obtained that the high-resolution XPS of the three-dimensional spectrum of Mo in the metal vacancy MXene-polyaniline composite material electrode shows 6 peaks near 229.50 eV, 231.00 eV, 232.41 eV, 232.79 eV, 234.05 eV, and 235.64 eV, corresponding to Mo-C, Mo 5+ and Mo 6+ respectively. During the discharge process of the mixed electrolyte from 1 mol / L to 0.1 mol / L, due to the introduction of protons, the valence state of Mo changes from +6 to +5, indicating that the energy storage mechanism of ammonium ions is the intercalation and deintercalation process of ammonium ions.

[0069] By observing the valence change of the Mo element and the change of the XRD signal under different charging voltages, observe Figure 6 and Figure 5 It is obtained that with the intercalation and deintercalation process of ammonium ions between the layers of the metal vacancy MXene-polyaniline composite material, obvious valence change behavior occurs in the Mo metal, indicating that efficient ammonium ion intercalation energy storage behavior is realized in the metal vacancy MXene-polyaniline composite material.

[0070] Cyclic voltammetry (CV) tests were performed in the potential range of -0.54 V to 0.30 V at scanning rates of 2 mV / s, 5 mV / s, 10 mV / s, 20 mV / s, 50 mV / s, 100 mV / s, 200 mV / s, and 500 mV / s, respectively. Galvanostatic charge-discharge (GCD) tests were carried out at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, 3 A / g, and 5 A / g. The tests of electrochemical performance also included electrochemical impedance spectroscopy (EIS) and stability tests.

[0071] Comparison Figure 7 with the (a) figure in 4 / 3 CT x , PANI, and metal vacancy MXene-polyaniline composite electrodes. From the cyclic voltammetry results of these three electrode materials at 10 mV / s, it can be seen that the metal vacancy MXene-polyaniline composite electrode exhibits a wider voltage window and an increased integral area of the CV curve, indicating the significant influence of PANI on MXene, promoting the occurrence of more electrochemical reactions, and thus being beneficial to the storage of ammonium ions. Observation Figure 7 of the (b) figure in Figure 7 shows that the electrochemical impedance spectrum of the metal vacancy MXene-polyaniline composite electrode presents a larger slope, indicating that the metal vacancy MXene-polyaniline composite electrode has the smallest charge transfer resistance, thereby accelerating the diffusion rate of ions in the electrolyte. From Figure 7 the (d) figure in

[0072] Combined Figure 7 with the results, it shows that the metal vacancy MXene-polyaniline composite provided by the present invention can be used in aqueous ammonium ion batteries, and its ammonium storage performance is greatly improved.

[0073] It should be noted that when the present invention involves numerical ranges, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the adopted step methods are the same as those in the embodiments, in order to prevent repetition, the present invention describes the preferred embodiments. Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the appended claims are intended to be construed as including the preferred embodiments and all changes and modifications falling within the scope of the present invention.

[0074] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a metal vacancy MXene-polyaniline composite material, characterized in that: The following steps are involved: Will Mo 4 / 3 Sc 2 / 3 AlC was etched to obtain multilayer MXene Mo 4 / 3 CT x ; Multilayer MXene Mo 4 / 3 CT x Intercalation treatment was performed to obtain a few-layer MXene Mo 4 / 3 CT x ; Aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x After mixing, in-situ polymerization is carried out to generate polyaniline, which is loaded on the few-layer MXene Mo 4 / 3 CT x On the nano-layered structure, a metal vacancy MXene-polyaniline composite material was obtained; Among them, aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x The mass ratio is 1:3:0.5:5~10.

2. The method for preparing a metal vacancy MXene-polyaniline composite material according to claim 1, characterized in that: Aniline, hydrochloric acid, ammonium persulfate and few-layer MXene Mo 4 / 3 CT x The mass ratio is 1:3:0.5:

8.

3. The method for preparing a metal vacancy MXene-polyaniline composite material according to claim 1, characterized in that: The conditions for the in-situ polymerization reaction are: stirring at -5°C to 0°C for 12h to 15h.

4. The method for preparing a metal vacancy MXene-polyaniline composite material according to claim 1, characterized in that: The etching process is as follows: hydrofluoric acid and Mo 4 / 3 Sc 2 / 3 After AlC is mixed, stir at 30℃~35℃ for 24h~36h; Among them, hydrofluoric acid and Mo 4 / 3 Sc 2 / 3 The mass ratio of AlC is 4.8-10.2:1-2.

5. The method for preparing a metal vacancy MXene-polyaniline composite material according to claim 1, characterized in that: The intercalation method is: to add multilayer MXene Mo 4 / 3 The intercalating agent is added to CTx, mixed evenly, and then centrifuged and washed to obtain; Among them, the intercalation agent and the multilayer MXene Mo 4 / 3 CT x The dosage ratio is 5mL~7mL:1g~2g.

6. The method for preparing a metal vacancy MXene-polyaniline composite material according to claim 5, characterized in that: The intercalant is selected from a cationic surfactant or an organic base.

7. The method for preparing a metal vacancy MXene-polyaniline composite material according to claim 6, characterized in that: The organic base is selected from tetrabutylammonium hydroxide, isopropylamine or n-butylamine.

8. A metal vacancy MXene-polyaniline composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The metal vacancy MXene-polyaniline composite material according to claim 8, characterized in that: In the metal vacancy MXene-polyaniline composite material, the metal vacancy MXene and polyaniline are in situ composited, the polyaniline is lamellar, and the lamellar polyaniline is vertically dispersed on the surface of the MXene layer.

10. Use of the metal vacancy MXene-polyaniline composite material according to claim 8 in preparing a positive electrode material for an aqueous ammonium ion battery.